2013
DOI: 10.1073/pnas.1211533110
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise induces independent shifts in call frequency and amplitude within the Lombard effect in echolocating bats

Abstract: The Lombard effect, an involuntary rise in call amplitude in response to masking ambient noise, represents one of the most efficient mechanisms to optimize signal-to-noise ratio. The Lombard effect occurs in birds and mammals, including humans, and is often associated with several other vocal changes, such as call frequency and duration. Most studies, however, have focused on noisedependent changes in call amplitude. It is therefore still largely unknown how the adaptive changes in call amplitude relate to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
103
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 55 publications
15
103
3
Order By: Relevance
“…Thus, the Lombard effect is fundamentally different from the Fletcher effect and does not require a comparison of internal forward model predictions with the sensory feedback. Our results are in line with the data from an earlier study on another bat species (Rhinolophus ferrumequinum) that exhibited the Lombard effect in the first call after noise onset (26). However, the term reflex should not be interpreted as that the Lombard effect is a fixed response to background noise.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the Lombard effect is fundamentally different from the Fletcher effect and does not require a comparison of internal forward model predictions with the sensory feedback. Our results are in line with the data from an earlier study on another bat species (Rhinolophus ferrumequinum) that exhibited the Lombard effect in the first call after noise onset (26). However, the term reflex should not be interpreted as that the Lombard effect is a fixed response to background noise.…”
Section: Discussionsupporting
confidence: 92%
“…The Lombard effect was first described over a century ago and is among the most widely studied audio-vocal integration phenomena. The response latency of the Lombard effect was estimated to be about 150-175 ms for humans (23,24), 150 ms for birds (25), and less than 150 ms for bats (26). There are at least two possible explanations for the overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…In species that display vocal plasticity, such as birds, bats and cetaceans, shifts in call frequency can help achieve this and geographical variation in these call parameters has been linked to natural variation in ambient noise levels from biotic and abiotic factors (Brumm & Slabbekoorn, 2005;Foote & Nystuen, 2008;Hage, Jiang, Berquist, Feng, & Metzner, 2013;Mossbridge, Shedd, & Thomas, 1999). Elevated anthropogenic noise levels may also promote these frequency shifts (Ansmann et al, 2007;Lesage, Barrette, Kingsley, & Sjare, 1999;Luís, most noise in the low-to mid-frequency ranges (Jensen et al, 2009;Lemon et al, 2006;Lesage et al, 1999) and several studies focused on cetacean vocal parameters have identified an upward frequency shift or increase in minimum or mean frequency associated with boat presence (Lesage et al, 1999;Luís et al, 2014;Parks et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One potential limitation to plasticity is the tight coupling between RF and the acoustic fovea in high duty cycle bats, like R. damarensis , that use Doppler shift compensation (Neuweiler, 1984; Schnitzler & Denzinger, 2011). However, HDC bats are able to shift their RFs (up to 3.9 kHz) in response to both neighboring conspecifics and different ambient noise conditions (Hage, Jiang, Berquist, Feng, & Metzner, 2013; Hiryu et al., 2006). Although small, such shifts in frequency encompass the differences between the mean RFs of neighboring populations of R. damarensis and may allow bats to optimize their detection range under the local climatic conditions without a change in allele frequency.…”
Section: Discussionmentioning
confidence: 99%